PP.06.22: AMPLIFICATION BLOOD PRESSURE CHARACTERIZATION IN YOUNG HEALTHY MALES. (June 2015) - Koretzky, M.; Obregon, S.; Huguet, E.; Haehenel, M.; Brandani, L.; Cadenas, M.; Vaisbuj, F.; Dulude, E. Perasso; Kotliar, C.
Abstract : Objective: Reference values for central blood pressure and its amplification in a general healthy population have been described by A. Herbert et al (Eur Heart Jour 2014). These large study and others authors as well, have characterized young males as showing a higher blood pressure amplification pattern. Authors have proposed that this condition could increase young subjects risk of presenting spurious systolic hypertension and that this would be at least partially related to an hyperkinetic heart. Our AIMS were to evaluate the amplification blood pressure pattern in young healthy males and to determine its association with cardiac index and glucemia as its physiological mechanism or consequences. Design and method: We evaluated 140 normotensive, non treated, healthy subjects, from 18 to 76 years old, in the context of a primary cardiovascular prevention program. Determinations of cardiac index and pulse wave velocity were obtained by non-invasive measurements (Mobil-O-Graph TM ), BP amplification rate was calculated and biochemical determinations were obtained in a 12 hour-fasting blood sample. Results: After applying exclusion criteria (diabetes, metabolic syndrome, new onset hypertension, drug treatment, thyroid abnormalities) we finally included 30 subjects and classified them into age tertiles (18-44; 45–64, >65). Male sex was correlated with higher amplification than females in all age groups, but strongly in the youngers (inverse linear correlation -0.133, p:0.001). A positive direct linear correlation was observed between amplification-glucemia (0.202, p:0.001) and amplification-cardiac index (0.224, p:0.001). Multivariate analysis demonstrated that sex, cardiac index and glucemia were associated with amplification in all groups with higher predictive value in the youngers. Conclusions: Our pilot sample-study contributes to test the hypothesis proposing that those amplification increased values described in young healthy males could be related to a hyperkinetic condition which seems to be also related with higher glucemia, although into normal rank. While autonomic disbalance can partially explained this data (hemodinamic pattern and disglucemia), we consider that its clinical implication could be a spurious hypertension phenomena that should be identified in this subjects.